Biomonitoring of Heavy Metal Cadmium in Spermonde Islands Waters Makassar Using Bioindicator of Starfish (Protoreaster nodosus) - Gita Permata Sari; Alfian Noor; Musa Ramang (Marina Chimica Acta, 2014)
This research aims to develop biomonitoring methods in terms of the development of marine life that can be used as bio-indicators of marine pollution. The analysis was optimized by means of samples taken from three different locations of the Barranglompo island waters, using AAS as an analysis technique. The analysis showed that cadmium content of heavy metals in starfish was 0.9916 ppm at the point I (05002’35,1” south latitude and 119019’46,1” north latitude), 1.0355 ppm at point II (05002’32,5” south latitude and 119019’44,3” north latitude) and 0.7889 ppm at point III (05002’29,4” south latitude and 119019’44,0” north latitude) in Spermonde Islands waters, particu- larly in Barranglompo island waters.